2024
DOI: 10.3390/socsci13030176
|View full text |Cite
|
Sign up to set email alerts
|

Professional Skills in Family Support: A Systematic Review

Rita dos Santos,
Anita Burgund Isakov,
Cátia Martins
et al.

Abstract: Family support encompasses a wide variety of professionals, sectors, and intervention paradigms that make it difficult to systematize and standardize the skills needed by the family support workforce. The present study aimed to describe the relevant skills of professionals, organize the main skills into different categories, and contribute to the development of intervention standardization guidelines in the field of family support. So, a systematic literature review was conducted following the PRISMA guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…The quantitative data collected also indicated that most participants highly agreed with having their interests and needs considered by the Facilitator. Mutual listening, openness, and adaptability towards families' needs and strengths can potentiate establishing trustful relationships with families, which has been identified as pivotal to enhancing the outreach and implementation quality of family and parenting support interventions (Anders et al, 2019;Cohen et al, 2020;dos Santos et al, 2024;Jiménez et al, 2024). Furthermore, integrating relational practices (e.g., approachability and listening to families) and participatory practices (e.g., replying to the concerns and priorities of families) into how practitioners work with families can positively impact parent, family, and child behaviour and functioning (Dunst et al, 2007).…”
Section: Views Regarding the Modelmentioning
confidence: 99%
“…The quantitative data collected also indicated that most participants highly agreed with having their interests and needs considered by the Facilitator. Mutual listening, openness, and adaptability towards families' needs and strengths can potentiate establishing trustful relationships with families, which has been identified as pivotal to enhancing the outreach and implementation quality of family and parenting support interventions (Anders et al, 2019;Cohen et al, 2020;dos Santos et al, 2024;Jiménez et al, 2024). Furthermore, integrating relational practices (e.g., approachability and listening to families) and participatory practices (e.g., replying to the concerns and priorities of families) into how practitioners work with families can positively impact parent, family, and child behaviour and functioning (Dunst et al, 2007).…”
Section: Views Regarding the Modelmentioning
confidence: 99%